Methodological considerations in the development of small area deprivation indices - Teljeur, Conor (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2007)
Health inequalities exist such that people with lower incomes and poorer social conditions experience poorer health. When individual level characteristics are aggregated to an area level, the socioeconomic status or deprivation of the neighbourhood also correlates with the health status and outcomes of the people who live in that area. The nature of these links between income and health vary across urban and rural areas reflecting the different social dynamics at play across the urban-rural continuum. The aim of this research was to assess current deprivation index methodology and to propose improvements to the methodology. In addition, the issues surrounding urban-rural variation in deprivation indices were addressed. To facilitate analysis of urban-rural deprivation differences, a small area classification was required. The previous urban-rural classification was based on a simple dichotomy which ignored the range of settlement and area types. Multiple data sources were used to develop a new multi-level urban-rural classification for small areas in Ireland. This classification provided better distinction between the variety of settlement types than the simple dichotomous classification and enabled a detailed analysis of regional bias.
Keywords: Public Health and Primary Care, Ph.D.; Ph.D. Trinity College Dublin